TERT promoter mutations are associated with poor prognosis and cell immortalization in meningioma. Issue 12 (11th July 2018) - Spiegl-Kreinecker, Sabine; Lötsch, Daniela; Neumayer, Katharina; Kastler, Lucia; Gojo, Johannes; Pirker, Christine; Pichler, Josef; Weis, Serge; Kumar, Rajiv; Webersinke, Gerald; Gruber, Andreas; Berger, Walter
Abstract: Background: Meningiomas are mostly benign tumors tending to progress to higher-grade lesions. Mutations in the telomerase reverse transcriptase ( TERT ) gene promoter are comparably rare in meningioma, but were recently suggested to predict risk of recurrence and progression. Here we have analyzed a cohort of World Health Organization grades I–III meningiomas regarding the impact of TERT promoter mutations on patient prognosis and in vitro cell propagation feasibility. Methods: From 110 meningioma patients, 128 tissue samples were analyzed for the TERT promoter mutations C228T and C250T by direct sequencing. Of the 128 samples, 121 were tested for cell propagation in vitro. Telomerase activity, TERT mRNA expression, and telomere lengths were investigated by telomeric repeat amplification protocol assay, reverse transcription PCR, and quantitative PCR, respectively. Impact of the E-twenty-six (ETS) transcription factor inhibitor YK-4–279 on cell viability and TERT promoter activity was analyzed. Results: TERT promoter mutations were found in 5.5% of all samples analyzed and were associated with a significantly upregulated telomerase activity and TERT mRNA expression ( P < 0.0001 both). Regarding telomere lengths, no significant difference between the TERT promoter wild-type and mutated subgroups was detected. Patients with TERT promoter mutated tumors exhibited significantly shorter overall survival ( P = 0.0006; 53.8 vs 115.6 mo). The presence of TERT promoter mutations but not telomerase activity or TERT mRNA expression predicted indefinite cell growth in vitro. TERT promoter mutated meningioma cells were hypersensitive against the ETS transcription factor inhibitor YK-4–279, inducing a distinct downregulation of TERT promoter activity. Conclusion: TERT promoter mutations drive meningioma aggressiveness, resulting in reduced patient survival, but might also open novel therapeutic options for progressive disease.